2021
DOI: 10.1029/2021gl094183
|View full text |Cite
|
Sign up to set email alerts
|

Recent Increases in Exposure to Extreme Humid‐Heat Events Disproportionately Affect Populated Regions

Abstract: Extreme heat can have devastating impacts on built and natural environments including crop losses, wildfire risk, infrastructure damage, and wildlife mortality (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 60 publications
(79 reference statements)
5
56
0
2
Order By: Relevance
“…Our findings of warming extreme TW values in many of the AR6 regions extend previous results indicating increases in humid heat extremes across the world (Raymond et al, 2020;Rogers et al, 2021) and in parts of Asia, Europe, and North America (C. Li, et al, 2017;Freychet et al, 2020;Mishra et al, 2020;X.-X. Li, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings of warming extreme TW values in many of the AR6 regions extend previous results indicating increases in humid heat extremes across the world (Raymond et al, 2020;Rogers et al, 2021) and in parts of Asia, Europe, and North America (C. Li, et al, 2017;Freychet et al, 2020;Mishra et al, 2020;X.-X. Li, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Extending those analyses, we use ERA5 reanalysis data to calculate trends in the intensity of extreme TW values for the land regions in the IPCC AR6 report (Iturbide et al, 2020). These regional-level results complement prior global-scale analyses and more process-oriented work (e.g., Freychet et al, 2020;Mishra et al, 2020;Rogers et al, 2021).…”
mentioning
confidence: 90%
“…This highlights that the threshold for deadly heat used here is rather extreme, and much lower thresholds are already considered as dangerous. On a daily timescales, TW has rarely exceeded 31 • C in the historical records [14], although some places have experienced hourly peaks above this value [15,16]. Previous studies have also shown that places such as South and East Asia could reach deadly TW conditions in the future under a 'business as usual' greenhouse gas emissions scenario [17].…”
Section: Introductionmentioning
confidence: 99%
“…Extreme events are of special importance in the study of heat stress because of their severe impacts. For example, some studies attempt to identify extremely rare, short‐term heat stress events in the past 30 years (Raymond et al., 2020; Rogers et al., 2021) and going into the future (Casanueva et al., 2020; Chen et al., 2020; Coffel et al., 2018; Im et al., 2017; Li et al., 2017; Pal & Eltahir, 2016). In order to quantify sWBGT/ESI biases in measuring extreme heat stress, we fit a generalized extreme value (GEV) model to the time series of annual maximum WBGT, sWBGT, and ESI (calculated from hourly frequency) during 1990–2019 using ERA5 reanalysis data.…”
Section: Methodsmentioning
confidence: 99%